An experimental and theoretical investigation of pure carbon dioxide absorption in aqueous sodium hydroxide in glass millichannels. (July 2018) - A, Durgadevi; S, Pushpavanam
Graphical abstract: Highlights: Method to reduce pure CO2 to useful products is introduced. Controlled study of reactive gas-liquid absorption in milli-channels. Limit of fast reaction i.e., mass transfer controlled regime is analysed. A model to determine the liquid side mass transfer coefficient is proposed. An empirical dimensionless correlation for mass transfer coefficient is obtained. Abstract: In this work, chemisorption experiments of pure CO2 (99% (v/v)) in different concentrations of sodium hydroxide solutions were carried out in a T-junction glass circular milli-channel in the slug flow regime. The absorption of the gas from the slug results in a shrinking of the slug as it moves along the channel. The rate of decrease of slug size and slug velocity are used to quantify the mass transfer rate. A lumped parameter model is developed to study the dissolution dynamics of CO2 slugs in the aqueous solution. The experimental data in this controlled study and the model developed are used to predict the liquid side volumetric mass transfer coefficient. The enhancement of mass transfer due to chemical reaction in the liquid phase is also quantified. The effect of various parameters like gas and liquid flow rates, concentration of NaOH on system behaviour is examined. An empirical correlation for dimensionless mass transfer coefficient is obtained from the experimental data which can be used to design absorption columns.